Antioxidant capacity in ice cream and dairy products - Campo-Banguero, Laura Marcela; Ramírez-Navas, Juan Sebastián (Revista Colombiana de Investigaciones Agroindustriales, 2021)
Currently, there is a global trend towards the consumption of foods that provide beneficial health effects. The leading research shows that using bioactive compounds derived from plants as a source of functional ingredients in food products can reduce the risk of degenerative diseases, managing to direct research mainly to the characterization of different types of fruits and their content of specific antioxidant components. Therefore, this review exposes the antioxidant power of functional ingredients in ice cream and some dairy products, showing their benefits on human health through their use in food products.